Effect of Topical Application of Apamargadi Ghrita for Utsadana - Granulation Tissue Formation in Dushta Vranam - Athira Soman; P.Benedict; Sreelekha M.P (International Journal of Ayurveda and Pharma Research, 2023)
Non-healing ulcers are defined as spontaneous or traumatic lesions, mainly in lower extremities that persist despite appropriate treatment and do not proceed towards healing in a defined time period. Wound healing is a very dynamic and complex process. It is divided into 5 stages in which granulation tissue formation, angiogenesis and synthesis of collagen occurs in the proliferative phase. On the basis of clinical features, non-healing ulcers can be considered as Dushtavrana in Ayurveda. Different types of Vrana and sixty types of treatment modalities are well explained in Susrutha Samhitha. Utsadana karma is indicated in non-healing ulcers with poor granulation tissue. It is the procedure by which the deep floor of the wound is elevated using drugs which promote growth of new tissues. Utsadana of Vrana can be correlated with the proliferation of new tissues in the wound healing process. The conservative and surgical management for non-healing ulcers mainly includes debridement, skin grafting and wound dressings. Even though these treatment methods help in healing the ulcer, the rate of recurrence is more due to the formation of unhealthy granulation tissue. Also it leads to complications like infection, sensory deficits, scarring and bleeding. Susruthacharya mentioned the drugs for Utsadana in Misrakadhyaya, they are Apamarga, Aswagandha, Suvarchala, Talapatri and drugs of Kakolyadi gana. Dalhana in his commentary mentioned Ghrita preparation of these drugs for topical application. Rasayana, Brimhana and Balya properties of these drugs will help in the formation of healthy granulation tissue. In the present case study a 30yr old male patient visited the OPD with non healing ulcer was selected for Utsadana karma. Daily dressing was done with Apamargadi ghrita. The study was done for a period of 30 days The dimensions and attributes of the ulcer was systematically measured on 1st, 8th, 15th, 30th day and the result was assessed. The result shows that topical application of Apamargadi ghrita is effective in Utsadana- granulation tissue formation of Dushta vrana.